Treatment of velopharingeal insufficiency with turn over mucoperiosteal palatal flap in a patient with DiGeorge syndrome - Kozarski, Jefta V; Veselinović, Mila; Djorović, Lazar; Mitrić, Biljana; Kozarski, Ksenija (Vojnosanitetski pregled, 2022)
Introduction. DiGeorge syndrome (velocardiofacial syndrome) occurs in about 1 in 4,000 people. It is characterized by incomplete gene penetration, due to which there is significant variability in the clinical picture in different patients. The paper describes the successful application of an inverted mucoperiosteal flap of the palate in a nine-year-old girl with DiGeorge syndrome who had pronounced velopharyngeal insufficiency (VPI). Case report. The girl was the first-born child from a normal pregnancy and a normal birth with a normal early psychomotor development. During breastfeeding, milk was occasionally returned to the nose, and later deviations from normal speech (incomprehensible and nasal speech) were noticed. At the age of 4, detailed genetic testing was performed and a microdeletion of 22q11 chromosome was found. Also, a submucosal cleft palate was established, and magnetic resonance angiography of the head and neck revealed an abnormal position of the left internal carotid artery (ICA) that extended submucosally to the central axis of the posterior wall of the pharynx. Then, the submucosal cleft palate was surgically resolved in other clinical center, but without speech improvement. Pharyngoplasty was not performed due to the risk of serious postoperative complications. It was explained to the parents that speech recovery will not be satisfactory without surgical treatment of VPI. At the age of 9, the girl was admitted to the Clinic for Plastic and Reconstructive Surgery and Burns of the Military Medical Academy in Belgrade for surgical treatment of VPI. Taking into account the potential risks of certain surgical methods, it was decided to perform intravelar veloplasty according to Furlow. Since it was intraoperatively found that the soft palate is too short and that this procedure cannot provide its sufficient length, the mucoperiosteal flap was lifted from the palate to the palatal aponeuroses on the posterior edges of the palatine bones leaving their oral surfaces exposed. The mucoperiosteal flap raised in this way could not also provide the required length of the soft palate only by retroposition. However, its length is 160% of the soft palate axis length, which was enough to turn over the front of the flap towards the pharynx of the soft palate to reach its posterior wall. The raised mucoperiosteal palatal flap has no muscles, so its motility was achieved by the fact that along the edges of the existing short and mobile palate, the flap was fixed to the existing palate and uvula. This provided the anatomical preconditions for speech recovery, shown during the one-year postoperative follow-up of the child. Exposed palatine bones and short palate was covered by mucosal tissue, without cystic formations. Conclusion. The mucoperiosteal palatal flap can be easily, successfully and maximally safely applied in the resolution of VPI in patients with DiGeorge syndrome where there is an aberrant submucosal position of the ICA. This flap could be a ʽflap of choiceʼ for such patients with atopic position of the ISA, too.